P348 3D reconstructions in complex fistulising perianal Crohn's disease to aid decision-making. (16th January 2018) - Sahnan, K; Adegbola, S O; Tozer, P J; Burling, D; Gupta, A; Warusavitarne, J; Faiz, O D; Phillips, R K; Hart, A L; Lung, P F
Abstract: Background: Perianal Crohn's fistulas are often complex, translating to difficult surgery and poor outcomes. MRI is the reference standard for assessment of perianal fistula, defining anatomy and guiding surgery. However, communication of findings between radiologist and surgeon remains challenging. Our aim was to use different forms and platforms to better understand complex perianal fistula through 3D imaging. Methods: Standard axial T2-weighted Spectral Attenuated Inversion Recovery (SPAIR) MRI sequences were acquired. Digital imaging and communications in medicine (DICOM) images of the MRI sequences were retrieved from the picture archiving and communication system (PACS) system and anonymized. DICOM images were imported onto validated open-source segmentation software. A specialist consultant gastrointestinal radiologist performed segmentation of the fistula tract, the internal and the external sphincter. Results: 3D models of the fistula tract and sphincter complex were created from several patients with complex perianal Crohn's fistulas. A combination of static images (Figure 1 and 2) and short animations were created (Figure 3). In addition, the reconstructions were uploaded onto an app to allow for manipulation of the images and also the removal of surrounding structures (Figure 4). Conclusions: A variety of platforms have been generated to improve accessibility to this technique. Accurate 3D reconstruction of complex perianal fistulas are feasible and have the potential to improve surgical understanding and decision-making, but also to augment training and aid patient comprehension for informed consent.